Prevention of progression to cirrhosis in hepatitis C with fibrosis: effectiveness and cost effectiveness of sequential therapy with new direct‐acting anti‐virals. Issue 8 (25th August 2016) - Faria, R.; Woods, B.; Griffin, S.; Palmer, S.; Sculpher, M.; Ryder, S. D.
Summary: Background: The new direct‐acting anti‐virals (DAAs) for hepatitis C virus (HCV) infection offer higher cure rates, but at a much higher cost than the standard interferon‐based treatments. Aim: To identify the cost‐effective treatment for patients with HCV infection with F3 liver fibrosis who are at high risk of progression to cirrhosis. Methods: A decision‐analytic Markov model compared the health benefits and costs of all currently licensed treatments as single treatments and in sequential therapy of up to three lines. Costs were expressed in pound sterling from the perspective of the UK National Health Service. Health benefits were expressed in quality‐adjusted life years. Results: Treatment before progression to cirrhosis always offers the most health benefits for the least costs. Sequential therapy with multiple treatment lines cures over 89% of patients across all HCV genotypes while ensuring a cost‐effective use of resources. Cost‐effective regimes for HCV genotype 1 patients include first‐line oral therapy with sofosbuvir–ledipasvir while peginterferon continues to have a role in other genotypes. Conclusions: The cost‐effective treatment for HCV can be established using decision analytic modelling comparing single and sequential therapies. Sequential therapy with DAAs is effective and cost‐effective in HCV patients with F3 fibrosis. This information is of significant benefit to health care providers with budget limitations and provides a sound scientific basis for drug treatment choices.